Variations of Time Irreversibility of Heart Rate Variability Under Normobaric Hypoxic Exposure - Li, Yang; Li, Jianqing; Liu, Jian; Xue, Yong; Cao, Zhengtao; Liu, Chengyu (Frontiers in Physiology, 2021)
In the field of biomedicine, time irreversibility is used for describing how imbalanced and asymmetric of biological signals. As one of important features of signals, the direction of time is always ignored. To find out the variation regularity of time irreversibility of heart rate variability (HRV) in the initial stage of hypoxic exposure, the present study implemented two hours’ acute normobaric hypoxic exposure on 6 young subjects who have no plateau or hypoxia experiences and oxygen concentration was set as 12.9%. Electrocardiogram (ECG) signals were recorded in the whole process and RR intervals sequences were extracted. Mathematical operations were executed to transform the difference of adjacent RR intervals into proportion and distance with delay time to conduct time irreversibility analysis of HRV. Same calculating method was implemented on 6 items randomly picked out from MIT-BIH normal sinus rhythm database as control group. Result shows that variation of time irreversibility of HRV in hypoxic environment is different from that in normoxic environment, time irreversibility indices of hypoxic group decreases continually at the delay time of 1 and 2, and indices curves of time irreversibility gradually tend to be steady and gather with each other at the delay time of 3 or 4. While control group shows no consistent tendency no matter what the delay time is in the range of 1 to 4. Our study indicates that in short-time hypoxic exposure, as hypoxic time goes by, regulation of cardiovascular autonomic nervous system weakens; regulation times and intensity of sympathetic and parasympathetic nerves tend to be equal.